PENGARUH SENAM REMATIK TERHADAP PENURUNAN NYERI REMATIK PADA LANSIA - Afnuhazi, Ridhyalla (Menara Ilmu, 2018)
Changes will occur on the body in line with increasing age. The circumstances of the caseit look on the system muskuloskletal and the other networks which will cause rheumaticdiseases. According to the WHO about the arthritis sufferer 2014 355 million peoplethroughout the world while in Indonesian rheumatism sufferers about 69.43 millioninhabitants. The refore implemented an arthritic gymnastics can decrease scale of pain insufferers of rheumatism. The type of research used Quasi experimental nature of pre-post testwith control group. The population in this research is elderly aged 60 to 80 years. The samplein this research totalled 16 people given gymnastics rheumatism. With the techniques ofsampling the sampling porpusive. This research has been conducted in april-may 2016.Dikumpulkandengan data using the observation sheets are then processed with computerizedanalyzed by Univariate and bivariat. The research results obtained on the implementation ofthe results of the univariate gymnastics rheumatism as many as 16 people. Result of thedecline in the scale of pain not significant after doing gymnastics rheumatism. The results ofstatistical tests in the get sign = 0.004 invisible means there is influence of gymnasticsrheumatism pain scale decline in the elderly Maternal Affection PSTW Batusangkar. Theconclusion to be drawn that there is a decreasing scale of pain after doing gymnasticsrheumatism on the elderly and also recommend to the elderly to routinely perform gymnasticsrheumatism.Keywords : Rheumatic, Rheumatic Gymnastics, Decreased Pain.